An Atypical Case of Extrapulmonary Presentation of SARS-Cov-2 Infection - Tun, Thet; Hannun, Merhej (Journal of Cardiovascular Medicine and Cardiology, 2020)
We present a case of a 26-year-old male who presented with diarrhoea, vomiting, chest pain and fever without respiratory symptoms including interstitial pneumonitis/pneumonia. He deteriorated with hypotension, persistently high fever and multiorgan involvement. Troponins were elevated and Electrocardiogram (ECG) showed non-specific T-wave and ST changes. Initial echocardiography showed severely reduced ejection fraction. He tested positive for a PCR nasopharyngeal swab for SARS‐CoV‐2. The patient recovered with about 10 days of only supportive care and his cardiac function returned to baseline, even though initial echocardiography had shown severely reduced left ventricular function. Although COVID-19 manifests primarily as a respiratory disease, few cases of cardiac injury without respiratory involvement have been reported. This case illustrates that COVID-19 can present atypically and affect multiorgan systems without significant respiratory system involvement.